Transtorno mental comum nos estudantes de medicina da Faculdade de Medicina de Botucatu-UNESP: uma análise longitudinal - Gryschek, Rebeca Jesumary Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Aim: Estimate the prevalence of common mental disorders among Botucatu Medical School's students on the first (2006) and last year (2011) of the medical course, and analyze its association with the explanatory variables. Methods: Longitudinal study based on a sample of Botucatu Medical School's students using a self-administered questionnaire answered in two moments of the medical course (2006 and 2011). Social-demographic characteristics, social support and common mental disorder were investigated. The dependent variable was the increasing score on the Self- Reporting Questionnaire (SRQ) when compared 2006 and 2011 data, analyzing its association with the exposure variables. On the multivariate analyses, it was built a Stepwise Logistic Regression model and p<0,05 was adopted to reject the nullity hypothesis. Results: In a class of 90 students, about 67.8% of the medical students have participated in the two moments. Among these, 31,2% (CI 95%: 19,2-43,1) achieved score level to common mental disorders on the beginning of the course and 37,7% (IC 95%: 25,2- 50,2) on the last year; nevertheless there was no significant difference between the two moments. On the multivariate analyses, adjusted for age, sex and 'considering giving up the medical course', those having a higher score on interaction-support scale in 2006 remain linked to a lower chance of rising on the SRQ score along the course (OR=0,84; CI 95% 0,72-0,99). Conclusion: Interactionsupport in 2006 demonstrated to be a protection factor related to the increasing SRQ score along the medical course. Considering the high prevalence of common mental disorder among the medical students, it is necessary more longitudinal and qualitative studies to increase the comprehension of the risk and protection factors associated with the mental illness of this population. The Medical School must pay attention to the undergraduate's mental health and promote changes through psychological ...

Objetivos: Estimar a prevalência de transtorno mental comum (TMC) entre os estudantes de medicina da Faculdade de Medicina de Botucatu (FMB) no primeiro (2006) e sexto (2011) anos do curso e analisar a associação com variáveis explanatórias. Método: Estudo longitudinal, realizado a partir de uma amostra de estudantes do curso de medicina da FMB em dois momentos, 2006 (1º. ano) e 2011(6º. ano). Foi utilizado questionário para autopreenchimento, investigando características sociodemográficas, apoio social e sofrimento psíquico. Foi estabelecido como desfecho o aumento do escore obtido no SRQ, quando comparado o ano de ingresso e o sexto ano, estudando-se sua associação com as variáveis de exposição. Para a análise multivariada, foi construído um modelo de Regressão Logística Stepwise tipo retrógrado e adotou-se o nível de significância estatística de 5% para rejeição da hipótese de nulidade. Resultados: Dos 90 estudantes que compõem a turma de alunos, 67,8% participou nos dois momentos (n=61). Dentre estes, 31,2% (IC 95%: 19,2-43,1) pontuou para TMC no início do curso e 37,7% (IC 95%: 25,2- 50,2) ao final do curso, não havendo diferença significativa entre os dois períodos. Na análise multivariada ajustada para idade, sexo e pensar em abandonar o curso; ter maiores pontuações na escala de apoio interação em 2006 se manteve associado à redução da chance de aumento nos escores no SRQ ao longo do curso (OR= 0,84, IC 95%: 0,72-0,99). Conclusões: Apoio interação em 2006 constitui-se um fator de proteção contra o aumento dos escores no SRQ ao longo do curso médico. Tendo em vista a alta prevalência de TMC entre os estudantes de medicina, faz-se necessário mais estudos longitudinais e qualitativos a fim de ampliar a compreensão dos fatores de risco e proteção associados ao adoecimento psíquico desta população. A Escola Médica deve estar atenta à saúde mental dos alunos por promover estratégias de ...
Common mental disorders among medical students of Botucatu Medical School-UNESP
Keywords: Depressão mental; Estudantes de medicina; Medicina e psicologia; Stress (Psicologia); Estudos longitudinais; Medicine and psychology